Edubot Project: Analyzing the Adaptation of Robotics Classes to the Remote Environment - Bottino, Giovanna Borges; Araújo, Sheila de Lima; Saigg, Caio de Lima; Matias, Mariana Costa Bernardes; Baptista, Roberto de Souza (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2021)
Given the need for social confinement in response to the global pandemic caused by the Covid-19 disease, the Edubot project made the transition from classroom teaching methodologies to distance learning methodologies. To assess the effectiveness of this adaptation, a survey was developed where new students, who has never studied with Edubot before, could give their opinion on affinity and quality with regard to the new classes. The answers could be analyzed and displayed in graphs. Interpreting them, it is evident that although the virtual classes are fulfilling what they promise, there is a preference for the in-person mode.